Assessment of electron transfer mechanisms during a long-term sediment microbial fuel cell operation - Peixoto, L. (2019)
The decentralized production of bioelectricity as well as the bioremediation of contaminated sediments might be achieved by the incorporation of an anode into anaerobic sediments and a cathode suspended in the water column. In this context, a sediment microbial fuel cell microcosm was carried out using different configurations of electrodes and types of materials (carbon and stainless steel). The results showed a long-term continuous production of electricity (>300 days), with a maximum voltage of approximately 100 mV reached after ~30 days of operation. A twofold increase of voltage was noticed with a twofold increase of surface area (~30 mV to ~60 mV vs. 40 cm2 to 80 cm2), while a threefold increase was obtained after the substitution of a carbon anode by one of stainless steel (~20 mV to ~65 mV vs. 40 cm2 to 812 cm2). Cyclic voltammetry was used to evaluate sediment bacteria electroactivity and to determine the kinetic parameters of redox reactions. The voltammetric results showed that redox processes were limited by the diffusion step and corresponded to a quasi-reversible electron charge transfer. These results are encouraging and give important information for the further optimization of sediment microbial fuel cell performance towards the long-term operation of sediment microbial fuel cell devices.